Enhancing Learning Outcomes: Project-Based Learning with Fluidsim in Electric Motor Control System Circuit - Apriyanto, Raffie Alfandy; Haryudo, Subuh Isnur; Rijanto, Tri; Achmad, Fendi (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aims to: (1) find significant improvement on students’ learning outcomes on electric motor control system circuits using the Project-Based Learning (PjBL) model with FluidSIM software; and (2) find significant differences in learning outcomes between Electrical Power Installation Engineering (TITL) students taught using PjBL with FluidSIM and conventional method. This experimental study employed a non-equivalent control group design. The experimental class (XI TITL 1) received treatment using PjBL with FluidSIM software, while the control class (XI TITL 2) used PjBL with the conventional method. Data were collected through assessments of learning outcomes and analyzed using t-tests to assess both improvements and differences. The results indicated significant improvements in learning outcomes for the experiment group following the implementation of PjBL using FluidSIM software. Additionally, a significant difference was found between the two groups’ learning outcomes, with a t value greater than the critical value (5.906 > 2.00). In conclusion, the PjBL model combined with FluidSIM effectively improves student learning outcomes.